Paintinggir Architecture: Designing a Coastal Area as a Painting Studio and Recess Area with a Sustainable Architectural Approach - Gladies Imanda Utami Rangkuty; Aprilia Chandrawati; Coral Aswanti; Maharanta Milala; Yovita Yolanda Budiman (Universitas Internasional Batam, 2021)
Painting is the activity of creating art using paint and canvas. According to qualitative method (Creswell, 2008) and correlational method, which is connecting the relations of the analysis results Batam is quite an advanced city and very close to the neighboring country, Singapore. However, there are not many places providing painting facilities in this small town. Planning painting studio by using high-rise buildings view from Singapore at Tanjung Pinggir Beach area will really support the mood of the artist or painter. The concept of 'paint' leads to the concept of 'Palette' and 'Paint drop' which are used as a reference for the main buildings of Paintinggir, Painting Studio and Recess Area. Paintinggir, a sustainable architectural design using pallete concept and paintdrop as a form of a development area, makes development with the purpose to provide tools, facilities and places for painters and connoiseurs of paintings.